Analysis of industrial contaminants in indoor air. Part 1. Volatile organic compounds, carbonyl compounds, polycyclic aromatic hydrocarbons and polychlorinated biphenyls - Barro, Ruth; Regueiro, Jorge; Llompart, María; García-Jares, Carmen (My University, 2024)
This article reviews recent literature on the analysis of industrial contaminants in indoor air in the framework of the REACH project, which is mainly intended to improve protection of human health and the environment from the risks of more than 34 millions of chemical substances. Industrial pollutants that can be found in indoor air may be of very different types and origin, belonging to the volatile organic compounds (VOCs) and semivolatile organic compounds (SVOCs) categories. Several compounds have been classified into the priority organic pollutants (POPs) class such as polychlorinated biphenyls (PCBs), polychlorinated dibenzo-p-dioxins and furans (PCDD/PCDFs) and related polychlorinated compounds, and polycyclic aromatic hydrocarbons (PAHs). Many of these compounds are partially associated to the air gas phase, but also to the suspended particulate matter. Furthermore, settled dust can act as a concentrator for the less volatile pollutants and has become a matrix of great concern for indoors contamination. Main literature considered in this review are papers from the last 10 years reporting analytical developments and applications regarding VOCs, aldehydes and other carbonyls, PCBs, PCDDs, PCDFs, and PAHs in the indoor environment. Sample collection and pretreatment, analyte extraction, clean-up procedures, determination techniques, performance results, as well as compound concentrations in indoor samples, are summarized and discussed. Emergent contaminants and pesticides related to the industrial development that can be found in indoor air are reviewed in a second part in this volume.
Keywords: Indoor air; Dust; Industrial contaminants; Air analysis; VOCs; Aldehydes; PCBs; PAHs